Complete intraventricular migration of the ventriculoperitoneal shunt - Basaran Gundogdu, Elif; Ozsoy, Ufuk; Tuzun, Yusuf (The European Research Journal, 2017)
Intracranial migration of the ventriculoperitoneal shunt is an extremely rare situation. A 2-month-old infant who had undergone ventriculoperitoneal shunt for hydrocephalus in the neonatal period presented with feeding problems and increasing head circumference. There was intracranial migration on cranial computed tomography and shunt survey images. Endoscopically the shunt was removed and a new shunt was applied. The patient was discharged with cure. This extremely rare shunt complication and its surgery both have serious complications. Therefore, the surgical technique, proper fixation of the shunt and the use of the right shunting material are significantly important.